Estudo das principais direções do fluxo subterrâneo no carste de Nobres/MT - Pedro, Paloma Dondo Tonello (2018)
The karst aquifers, the object of this research, are formed in soluble rocks and are characterized by the presence of enlarged fractures and conduits, which form a hydraulic connection, characterizing an underground drainage network. These are areas very conducive to the action of the processes of dissolution, in a way more intensified before the other lithologies. In this way, the karst regions can present a rapid transport of pollutants in their conduits. In addition to geotechnical problems such as subsidence and collapse. Considering the aforementioned characteristics, the area of study located in the municipality of Nobres becomes an important object of study. This municipality is rich in tourist attractions due to the beauties characteristic of karst regions and related to water resources, as upwellings. Thus, in view of the natural constraints of kestrels and the lack of studies on Nobres/MT, the need arises for a study to unify the information, providing an overview of the emergence of the area, especially related directions of the underground stream that feeds these features. Therefore, this work has to verify the main directions of the underground flow in the upwelling "Bate Palma" and to relate these directions with other emergencies analyzed. The methodology used for this research was based on the integration, compilation and interpretation of geophysical studies carried out in upwellings in the municipality of Nobres (MT). In addition, geophysical tests were carried out using the electrical resistivity method, using the electric walking technique. Before the construction of the contour maps for the parameters involved (resistivity and spontaneous potential), was obtained E-W, NNE-SSW and N-S directions of the underground flow. From the pseudosections and maps of apparent resistivities produced it was possible to verify smaller values in the more superficial portion of the substrate, and higher values in the greater depths, inducing, respectively, the existence of a saturated soil near the surface and carbonaceous rocks with few fractures and / or massive. In addition, the main directions of the underground flow, E-W, were perceptible in different depths analyzed from the electric path and confirmed in the map of spontaneous potential.